Comparative Study on Different Drying Methods of Fish Oil Microcapsules - Yuqi Pang; Xu Duan; Guangyue Ren; Wenchao Liu (Journal of Food Quality)
Microencapsulation is widely used to minimize the oxidation of fish oil products. This study compared the effects of different drying methods, for example, spray drying (SD), freeze drying (FD), and spray freeze drying (SFD) on the microencapsulation of fish oil. Spray drying (SD) is the most common method for producing fish oil microcapsules, and it has low operation cost and short processing time, while the product yield and quality are poor. Freeze drying (FD) can be used to produce oil microcapsules with high quality, but it takes long time and high overall cost for drying. Spray freeze drying (SFD) is a new method for the preparation of microcapsules, which combines the SD and FD processes to obtain high quality powder. The yield of powder reached 95.07% along with porous structure by SFD. The stability and slow-release property of SFD products were better than those of SD and FD, which showed that SFD improved product storage stability and potential digestibility.